Benguela Niños and Benguela Niñas in Forced Ocean Simulation From 1958 to 2015. Issue 8 (19th August 2019) - Imbol Koungue, Rodrigue Anicet; Rouault, Mathieu; Illig, Serena; Brandt, Peter; Jouanno, Julien
Abstract: A systematic study of Benguela Niño and Benguela Niña events during 1958 to 2015 including those that developed before the satellite era (1982) is carried out using an ocean general circulation model in combination with a linear equatorial model. Altogether, 21 strong warm and cold anomalous coastal events are identified among which 6 undocumented extreme coastal events are reported. Results suggest that most of these extreme coastal events including the newly identified ones are linked to remote equatorial forcing via mode 2 equatorial Kelvin waves. The latter propagates after approaching the African coast poleward as coastally trapped waves leading surface temperature anomalies along the Angola‐Benguela current system by one month. One to two months before the peak of Benguela Niños or Niñas usually occurring in March–April, a large‐scale wind stress forcing is observed with both local (variations of alongshore coastal wind stress) and remote forcing developing simultaneously. Results further suggest that surface temperature anomalies off Southern Angola and in the Angola‐Benguela Front are associated with equatorial dynamics and meridional wind stress fluctuations off the southwestern African coast north of 15°S. Similar mechanisms are observed for Northern Namibia in combination with forcing by local meridional wind stress variations. Plain Language Summary: The Benguela upwelling system located in the southeastern Atlantic Ocean supports a large marine ecosystem due to upwelling conditions. Every few years, anomalous warm and cold coastal events occur in the southeastern Atlantic and are detrimental for Angola, Namibia, and South Africa, as they affect fisheries and rainfall like El Niño phenomenon in the Pacific. To study these coastal events from 1958 to 2015, we use the output from a tropical Atlantic simulation in combination with the solution of a simple linear equatorial model. We study the anomalous coastal events including the ones that occurred before the satellite era (before 1982) and examine the role of the local wind forcing and the remote forcing associated with equatorial variability. We describe so far undocumented extreme events occurring from 1958 to 2015. Results suggest that most of the extreme coastal warm and cold events are associated with the propagation of equatorial Kelvin waves along the equatorial waveguide which trigger poleward‐propagating coastal trapped waves along the southwestern African coast. One to two months before the peak season (usually March–April) of the anomalous coastal events, a large‐scale wind pattern is observed, encompassing both variations of alongshore coastal wind in the southeastern Atlantic and zonal wind along the equatorial Atlantic. Key Points: Over 1958–2015, we document the development of Benguela Niño and Niña events occurring along the southwestern African coast They are associated with coastally trapped waves dominantly forced by eastward propagating equatorial Kelvin waves of second baroclinic mode They are linked to large‐scale wind stress forcing one to two months before they peak usually in March–April